Implementasi Kebijakan E-Government dalam Administrasi Kepegawaian - M Harry Mulya Zein; Diskha Febriyan Prasutra; Sisca Septiani (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
The implementation of E-Government policies in personnel administration aims to improve the efficiency and transparency of public services. This research analyzes the implementation of related policies, obstacles faced, and solutions taken. The method used is descriptive qualitative with an inductive approach, where data is obtained through observation, interviews, and documentation. The results show that although the implementation of E-Government is going well, there are still obstacles, such as the lack of experts and adequate infrastructure. Efforts made include recruitment of experts and updating technological infrastructure. In conclusion, improving the implementation of E-Government needs to be done by paying attention to the existing supporting factors.